Assessment of morphological variation and association studies in Litsea glutinosa (Lour.) C.B. Rob. from Central India. (17th February 2020) - Mohammad, Naseer; Sonkar, Mukesh; Pardhi, Yogesh; Rana, PK; Dahayat, Ankur
ABSTRACT: Litsea glutinosa (Lour.) C.B. Rob., one of the important non-timber forestry species in Central India, is represented by highly fragmented populations and has been drastically reduced for the last 40 years, promulgating government ban on its extraction. In the present investigation, we investigated variation for important morpho-metric traits, i.e. tree height (m), clear bole height (m), girth at breast height (cm), crown radius (m), crown diameter (m), crown height (m), number of primary branches, leaf area (cm 2 ), leaf weight (gm), specific leaf area (cm 2 /g), bark wt/unit area (g), and their relationship. Investigation revealed existence of high level of variation for clear bole height, crown diameter, girth at breast height, and crown radius. A critical perusal of character correlation and path analysis revealed that tree height followed by crown radius, girth at breast height, and number of branches had the highest positive direct effect on bark weight/unit area. These traits should be included in the selection criteria for L. glutinosa . The observed high estimates of genetic variation for morpho-metric traits are, however, in contrast to the established relationship between genetic variation and population size. Populations of Balaghat and Chhindwara localities should be given due considerations for in situ conservation as they are in viable numbers and grouped in major clusters.